2022
DOI: 10.1371/journal.pcbi.1010716
|View full text |Cite
|
Sign up to set email alerts
|

The geometry of representational drift in natural and artificial neural networks

Abstract: Neurons in sensory areas encode/represent stimuli. Surprisingly, recent studies have suggested that, even during persistent performance, these representations are not stable and change over the course of days and weeks. We examine stimulus representations from fluorescence recordings across hundreds of neurons in the visual cortex using in vivo two-photon calcium imaging and we corroborate previous studies finding that such representations change as experimental trials are repeated across days. This phenomenon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
4
8
0
Order By: Relevance
“…oriented gratings) (Marks & Goard, 2021). Importantly, representational drift can occur despite sustained decoding accuracy of the target content from neural responses by a linear classifier (Aitken et al, 2022), as we observed in the present study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…oriented gratings) (Marks & Goard, 2021). Importantly, representational drift can occur despite sustained decoding accuracy of the target content from neural responses by a linear classifier (Aitken et al, 2022), as we observed in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Representational drift has been observed in the hippocampus (Ziv et al, 2013) and also in cortical regions (Driscoll, Pettit, Minderer, Chettih, & Harvey, 2017), including sensory cortex (Aitken, Garrett, Olsen, & Mihalas, 2022; Deitch et al, 2021), when observers are exposed to similar stimuli across sessions and days. Representational drift is higher for more complex representations associated with naturalistic stimuli relative to simple items (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Representational drift (Aitken et al, 2022; Deitch et al, 2021; Marks and Goard, 2021; Rule et al, 2019; Schoonover et al, 2021) could also contribute to differences in coding across days. However, several control analyses comparing cluster sizes to shuffled conditions (Extended Data Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, assemblies of tightly connected neurons can compete for simple and robust representations of information carried by stimuli. As the identity of the assembly may change over time, which neuronal assembly gets recruited and wins over the rest may not matter 78,79 .…”
Section: Discussionmentioning
confidence: 99%